INFLUENCE OF ATTITUDINAL LOYALTY ON ONLINE IMPULSE BUYING WITH SELF-CONTROL AS A MODERATING VARIABLE - Ali Wardhana; Nicholas Marcelino (Universitas Nusa Cendana, 2026)
This study aims to analyze the effect of attitudinal loyalty on online impulsive buying, with self-control acting as a moderating variable. A quantitative approach was employed by collecting data from 85 respondents who had shopped through e-commerce platforms in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach to test the proposed hypotheses. The results indicate that attitudinal loyalty has a significant effect on impulsive buying behavior, suggesting that stronger emotional attachment and favorable attitudes toward an online platform may increase spontaneous purchasing tendencies. Furthermore, self-control significantly moderates the relationship between attitudinal loyalty and impulsive buying with negative direction, meaning that individuals with higher self-control are less likely to engage in impulsive purchases even when they exhibit strong loyalty. Interestingly, among the dimensions of the online shopping experience, only ease of navigation and trust significantly influence attitudinal loyalty. This finding suggests that functional efficiency and perceived security play a more crucial role in building consumer loyalty than purely hedonic factors such as enjoyment. Overall, the study highlights the importance of platform usability and trust-building strategies while also emphasizing the role of individual psychological traits in shaping impulsive buying behavior. Keywords: Attitudinal Loyalty; Impulsive Buying; Self-Control; E-Commerce; Online Shopping Experience